Identification of the presence of ischaemic stroke lesions by means of texture analysis on brain magnetic resonance images. (June 2019) - Ortiz-Ramón, Rafael; Valdés Hernández, Maria del C.; González-Castro, Victor; Makin, Stephen; Armitage, Paul A.; Aribisala, Benjamin S.; Bastin, Mark E.; Deary, Ian J.; Wardlaw, Joanna M.; Moratal, David
Highlights: Radiomics in conventionally segmented tissues can identify MRI scans that had a stroke. Patient's advanced age can negatively influence classification results. Feature selection and stroke subtype influence but do not determine accuracy. Stroke subtype cannot be ascertained from texture analysis in brain tissues. Abstract: Background: The differential quantification of brain atrophy, white matter hyperintensities (WMH) and stroke lesions is important in studies of stroke and dementia. However, the presence of stroke lesions is usually overlooked by automatic neuroimage processing methods and the-state-of-the-art deep learning schemes, which lack sufficient annotated data. We explore the use of radiomics in identifying whether a brain magnetic resonance imaging (MRI) scan belongs to an individual that had a stroke or not. Materials and methods: We used 1800 3D sets of MRI data from three prospective studies: one of stroke mechanisms and two of cognitive ageing, evaluated 114 textural features in WMH, cerebrospinal fluid, deep grey and normal-appearing white matter, and attempted to classify the scans using a random forest and support vector machine classifiers with and without feature selection. We evaluated the discriminatory power of each feature independently in each population and corrected the result against Type 1 errors. We also evaluated the influence of clinical parameters in the classification results. Results: Subtypes of ischaemic strokes (i.e. lacunar vs. cortical) cannot be discerned using radiomics, but the presence of a stroke-type lesion can be ascertained with accuracies ranging from 0.7 < AUC < 0.83. Feature selection, tissue type, stroke subtype and MRI sequence did not seem to determine the classification results. From all clinical variables evaluated, age correlated with the proportion of images classified correctly using either different or the same descriptors (Pearson r = 0.31 and 0.39 respectively, p < 0.001). Conclusions: Texture features in conventionally automatically segmented tissues may help in the identification of the presence of previous stroke lesions on an MRI scan, and should be taken into account in transfer learning strategies of the-state-of-the-art deep learning schemes.